EVALUASI KONTEKS KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN SIDENRENG RAPPANG - Lukman Lukman; Akmal Ibrahim; Nur Indrayati Nur Indar; Muh Tang Abdullah (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
As a form of overcoming the problem of wastes, Sidenreng Rappang Regency had a Regional Regulation No.7 LD.2016/TLD.2016/NO.49 about Waste Management, which states that in order to improve the public health, realize a clean and healthy environmental, it's necessary to carry out management in an integrated and comprehensive manner from upstream to downstream. than in the context of comprehensive and integrated waste management, it's necessary to need the participation of the community with a proportional, effective and efficient manner. The purpose of this research is to determine the policy context of terms the policy evaluation of the waste management program in Sidenreng Rappang Regency. The method of research was carried out with data collection techniques, observations, and interviews with several informants. The type is descriptive qualitative using Miles and Huberman analysis techniques, that is namely data reduction, data display, and conclusion drawing. The results showed that the policy of program was not effective or was achieved due to lack of attention and control from the institution concerned, lack of socialization to the community, less TPS and TPA causing more indiscriminate disposal of waste, the schedule of operational disposal often experienced delays and had not been good implemented by the community , the existence of a waste bank that is increasingly lacking, and public awareness of waste management is tiny.